Gender-Responsive Government Budgeting - Sarraf, Feridoun (IMF Working Papers; Working Paper ;, 2003)
This paper examines the concept of gender-responsive government budgeting, promoted in recent years by women's nongovernmental organizations, academia, and multilateral organizations, and the extent of its implementation by national governments in both advanced and developing countries. Owing to recently developed analytical and technical tools, government budget management systems in some countries can help promote gender equality-to the extent of government involvement in gender-sensitive sectors and programs-at any level of available funding. However, to be fully effective, obstacles such as gender-biased culture, the lack of appropriate budget classifications, and the lack of gender analysis expertise and gender-disaggregated data in most countries need to be addressed.